The Inventory of the Estate farm Senkoniai - Stasys Pamerneckis; Roberta Sakalauskaitė (Lietuvos Istorijos Studijos)
The geometrical (land measuring) inventory of the Estate farm Senkoniai, which once belonged to the Karpis family and is kept at the Manuscript Department of Vilnius University Library, is being presented in this summary. It is characterized by the relative sufficiency of data about peasant farms, minuteness of description, and the addition of 12 land plans in good condition.